Comparison of the sensitivity of mass spectrometry atmospheric pressure ionization techniques in the analysis of porphyrinoids. (3rd October 2013) - Świder, Paweł; Lewtak, Jan P.; Gryko, Daniel T.; Danikiewicz, Witold
<x xml:space="preserve">Abstract</x> The porphyrinoids chemistry is greatly dependent on the data obtained in mass spectrometry. For this reason, it is essential to determine the range of applicability of mass spectrometry ionization methods. In this study, the sensitivity of three different atmospheric pressure ionization techniques, electrospray ionization, atmospheric pressure chemical ionization and atmospheric pressure photoionization, was tested for several porphyrinods and their metallocomplexes. Electrospray ionization method was shown to be the best ionization technique because of its high sensitivity for derivatives of cyanocobalamin, free‐base corroles and porphyrins. In the case of metallocorroles and metalloporphyrins, atmospheric pressure photoionization with dopant proved to be the most sensitive ionization method. It was also shown that for relatively acidic compounds, particularly for corroles, the negative ion mode provides better sensitivity than the positive ion mode. The results supply a lot of relevant information on the methodology of porphyrinoids analysis carried out by mass spectrometry. The information can be useful in designing future MS or liquid chromatography–MS experiments. Copyright © 2013 John Wiley & Sons, Ltd.